Mémoire du monde : patrimoine filmique national / Programme général d'information et UNISIST - ONUESC (1995)

Évaluation de procédés commerciaux de désacidification de masse - Tse, Season (Institut canadien de conservation (ICC), 1995)
he evaluation of three mass deacification processes – Akzo-DEZ, Wei T’o and FMC-{MG}3 – is a five-part project that began in August 1991. The project, coordinated by Helen Burgess and the Metro Toronto Chairman’s Committee for Preserving Documentary Heritage (CCPDH), is funded by a large number of libraries, archives and institutions in Canada and the United States, and is supported by CCI. The goal is to identify the potential and limitations of the three mass deacidification processes. The results will provide technical information for institutions that are considering mass deacidification as a solution to the problem of acid papers. The five groups of materials to be studies are listed, a project description is given and some general observations and conclusions are made in this article.